2018
DOI: 10.1016/j.mam.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

ROS signaling and ER stress in cardiovascular disease

Abstract: The endoplasmic reticulum (ER) produces the vast majority of all proteins secreted into the extracellular space, including hormones and cytokines, as well as cell surface receptors and other proteins which interact with the environment. Accordingly, this organelle controls essentially all vital links to a cell's external milieu, responding to systemic metabolic, inflammatory, endocrine, and mechanical stimuli. The central role the ER plays in meeting protein synthetic and quality control requirements in the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
179
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(182 citation statements)
references
References 116 publications
(158 reference statements)
2
179
0
1
Order By: Relevance
“…B, Quantitative analysis of mean DCFH-DA fluorescence intensity in different groups using bar graphs. 11,14 It has been reported that ISO causes myocardial injury possibly by damaging mitochondrial function via altering mitochondrial membrane permeability and increasing production of ROS. D, Quantitative analysis of apoptotic cells in different groups using bar graphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…B, Quantitative analysis of mean DCFH-DA fluorescence intensity in different groups using bar graphs. 11,14 It has been reported that ISO causes myocardial injury possibly by damaging mitochondrial function via altering mitochondrial membrane permeability and increasing production of ROS. D, Quantitative analysis of apoptotic cells in different groups using bar graphs.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Among these, excessive accumulation of ROS could cause severe oxidative stress injury directly leading to cell death. 13,14 Hence, inhibiting ER stress-induced apoptosis maybe an effective way to alleviate myocardial injury. 11 A series of studies have shown that apoptosis in myocardial injury is also associated with endoplasmic reticulum (ER) stress injury.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that reactive oxygen species (ROS) are produced as a downstream event of ERS that can lead to cell death . We detected the ROS levels in hypoxic NMVMs by the dihydroethidium (DHE) assay.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have indicated that reactive oxygen species (ROS) are produced as a downstream event of ERS that can lead to cell death. 26 We detected the ROS levels in hypoxic NMVMs by the dihydroethidium (DHE) assay. Pretreatment with lenti-si lncRNA MEG3 reduced the increased number of DHE-positive NMVMs that were induced by hypoxia, indicating lower ROS levels (Figure 4E,F).…”
Section: Lncrna Meg3 Knockdown Inhibited Endoplasmic Reticulum Strementioning
confidence: 99%
“…The main purpose of the UPR is to restore endoplasmic reticulum function and promote cell survival; however, continuous or severe ERS activates apoptotic signalling, leading to apoptosis . Protein kinase R‐like endoplasmic reticulum kinase (PERK) is a transmembrane signal transducer of the endoplasmic reticulum and most closely related to oxidative stress . PERK promotes the over‐expression of CCAAT/enhancer binding protein homologous protein (CHOP) through activating transcription factor‐4 (ATF‐4), leading to apoptosis.…”
Section: Introductionmentioning
confidence: 99%